Humoral response in early stages on infection of cod (Gadus morhua L.) with atypical furunculosis - Begljót Magnadóttir 1943-; Berglind Gísladóttir 1981-; Sigríður Steinunn Auðunsdóttir 1984-; Birkir Þór Bragason 1972-; Sigríður Guðmundsdóttir 1950- (2010)
Atlantic cod (Gadus morhua) was experimentally infected with the bacterium Aeromonas salmonicida subsp. achromgenes (Asa), which causes atypical furunculosis in cod and other fish species. Uninfected fish and fish infected with two different bacterial dosages were used and blood samples collected before infection and after 1 and 6 days. The effect of infection on the following humoral parameters was determined: the total protein serum level, the concentration of cortisol, two types of pentraxins and IgM, and on the specific and natural antibody and anti-trypsin activity. The results showed that infection by Asa caused a significant increase in the stress hormone cortisol while other parameters showed limited and in general suppressive response to infection. Neither CRP PI nor CRP PII, the two types of cod pentraxins, acted as typical acute phase proteins in the early stages of infection. The short duration of the experiment may have influenced the limited response observed but the results also reflect the relatively slow immune response of cod. Þorskur (Gadus morhua) var sýktur með bakteríunni Aeromonas salmonicida undirteg. Achromogenes (Asa), sem veldur sjúkdómnum kýlaveikibróður í þorski og fleiri fisktegundum. Ósýktur fiskur og fiskur sýktur með tveim mismunandi skömmtum af Asa voru notaðir og blóðsýni tekin fyrir sýkingu og eftir 1 og 6 daga. Áhrif sýkingar á eftirfarandi vessabundna þætti í sermi voru könnuð: heildar magn prótína, cortisols, tveggja gerða af pentraxínum og IgM, og á virkni sérvirkra og náttúrulegra mótefna og ensímtálma. Niðurstöður sýndu að sýking olli umtalsverðri aukningu á streituhormóninu cortisól en hafði takmörkuð og frekar bælandi áhrif á aðra þætti. Hvorki CRP PI né CRP PII, tvær gerðir af bráðaprótínum (pentraxínum) sem greinst hafa í þorski, sýndu dæmigerð bráðasvarsviðbrögð í sýkingu. Stuttur tilraunatími hefur sennilega haft áhrif á þau takmörkuðu viðbrögð sem greindust en gefa einnig til kynna tiltölulega seinvirkt ónæmisviðbragð þorsks við sýkingu.